KONSEP GURUNYA MANUSIA DALAM PERSPEKTIF MUNIF CHATIB - uswatun hasanah (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
Human teacher is a teacher who has the sincerity in teaching and learning. Teachers who have confidence that the target job is to make the students managed to understand the material being taught. Teachers are sincere, will think if there are learners who do not understand the teaching materials. Teachers who tried to take the time to learn because they are aware, the teaching profession should not stop learning. Teachers have strong desire and serious to join the training and competence development. Human teacher should be able to look at the competence of the learners a wider, based on three capabilities, such as: cognitive abilities, psychomotor abilities and affective abilities. Five parcel gifts to be opened by a human teacher, namely: 1) star; 2) ocean; 3) treasure; 4) divers; and 5) talent.